The role of renal proximal tubule transport in the regulation of blood pressure - Shoko Horita; Motonobu Nakamura; Masashi Suzuki; Nobuhiko Satoh; Atsushi Suzuki; Yukio Homma; Masaomi Nangaku (The Korean Society of Nephrology, 2017)
The electrogenic sodium/bicarbonate cotransporter 1 (NBCe1) on the basolateral side of the renal proximal tubule plays a pivotal role in systemic acid-base homeostasis. Mutations in the gene encoding NBCe1 cause severe proximal renal tubular acidosis accompanied by other extrarenal symptoms. The proximal tubule reabsorbs most of the sodium filtered in the glomerulus, contributing to the regulation of plasma volume and blood pressure. NBCe1 and other sodium transporters in the proximal tubule are regulated by hormones, such as angiotensin II and insulin. Angiotensin II is probably the most important stimulator of sodium reabsorption. Proximal tubule AT1A receptor is crucial for the systemic pressor effect of angiotensin II. In rodents and rabbits, the effect on proximal tubule NBCe1 is biphasic; at low concentration, angiotensin II stimulates NBCe1 via PKC/cAMP/ERK, whereas at high concentration, it inhibits NBCe1 via NO/cGMP/cGKII. In contrast, in human proximal tubule, angiotensin II has a dose-dependent monophasic stimulatory effect via NO/cGMP/ERK. Insulin stimulates the proximal tubule sodium transport, which is IRS2-dependent. We found that in insulin resistance and overt diabetic nephropathy, stimulatory effect of insulin on proximal tubule transport was preserved. Our results suggest that the preserved stimulation of the proximal tubule enhances sodium reabsorption, contributing to the pathogenesis of hypertension with metabolic syndrome. We describe recent findings regarding the role of proximal tubule transport in the regulation of blood pressure, focusing on the effects of angiotensin II and insulin.